Peran Penyuluh Agama dalam Mencegah Politisasi Agama Menjelang Tahun Politik 2024: The Role of Religious Counselor in Preventing the Politization of Religion Toward the 2024 Political Year - Solechan, Achmad; Luthfi Zuhdi , Muhammad; Syauqillah, Muhammad (Direktorat Jenderal Bimbingan Masyarakat Islam, 2023)
Religion is one of the national elements that binds national harmony. Approaching the 2024 political year, various parties contesting in the legislative and executive elections are trying to make various efforts to become winners. One of the efforts to win this contest is to practise politicization of religion. In fact, political experts have agreed that the politicization of religion is not a good thing for a pluralistic country like Indonesia. Therefore, in order to avoid the negative impact of the politicization of religion, various parties, including religion counselors, should try to prevent it. The limited number of articles and research on the role of religion counselors in preventing the negative impact of the politicization of religion prompted the author to focus the research on the role of religion counselors in preventing the negative impact of the politicization of religion. This research seeks to provide insight to religion counselors about their crucial role in preventing the negative impacts of politicization of religion. This research uses a qualitative method with a descriptive approach. Data taken from a literature study with primary data: Joint Decree among the Minister of Religion of the Republic of Indonesia and the Head of the State Civil Service Agency number: 574 of 1999 and Number: 178 of 1999. The results of this research are that religion counselors have four roles in preventing the negative impacts of politicization of religion, namely: roles informative-educative roles, consultative, advocative and administrative roles.